Human papillomavirus-related multiphenotypic sinonasal carcinoma. Issue 1 (February 2023) - Morishita, Yohei; Sakashita, Shingo; Tomioka, Toshifumi; Okano, Wataru; Shinozaki, Takeshi; Higashino, Takuya; Matsuura, Kazuto; Hayashi, Ryuichi
Abstract: Human papillomavirus-related multiphenotypic sinonasal carcinoma (HMSC) is a rare primary tumor of the sinonasal tract that has been reported recently. It is reportedly associated with human papillomavirus infection. The tumor presents with glandular cyst-like histology, but some cases exhibit squamous epithelialization and are positive on p16 immunohistochemical staining. The clinical picture and treatment of this disease have not been established. However, this report describes a recurrent case of this disease treated with salvage surgery. The patient was a 61-year-old woman who presented to the previous doctor with a chief complaint of nasal obstruction. A localized tumor was found in the left nasal cavity and was resected under endoscopic guidance. The postoperative pathological diagnosis was HMSC. Twenty-one months after the surgery, local recurrence was observed, and the patient was referred to our hospital. Since the recurrent lesion had widely infiltrated outside the nasal cavity, extensive resection and reconstructive surgery were performed. Postoperative radiotherapy was performed as an additional treatment. Notably, 13 months have passed since the salvage surgery, and no recurrence has been observed to date.